Expanding the Phenotypic Spectrum of SPG7 Rare Damaging Variants Insights From a Hungarian Cohort - Jimoh Idris János; Balicza Péter; Szlepák Tamás; Csabán Dóra; Gál Anikó; Géresi Adrienn; Grosz Zoltán; Palásti Ágnes; Boczán Judit; Klivényi Péter; Molnár Mária Judit (2025)
Mitochondria-associated paraplegin dysfunction is primarily linked to spastic paraplegia; however, genetic alterations in SPG7 have been associated with a broader spectrum of clinical symptoms. To identify disease-causing variants in the SPG7 gene, 437 patients with spastic ataxia, mitochondrial dysfunction-associated symptoms, or motoneuron lesions detected by EMG have been tested. We aimed to assess the clinical spectrum and determine the frequency of damaging variants within patient groups, particularly those less studied. Using ACMG criteria, we identified 10 pathogenic or likely pathogenic variants, 5 variants of uncertain significance with predicted damaging effects, and a probable risk factor variant in 58 patients. We identified 25 biallelic and 33 monoallelic cases. The most common variant was p. Leu78Ter (N = 23), followed by p. Ala510Val (N = 21). The point prevalence of SPG7-associated conditions in Hungary in 2024 is 0.46 per 100 000. In addition to well-characterized cohorts, SPG7 alterations were frequently identified in cohorts with multisystemic mitochondrial disease and lower motoneuron lesions. Multiple mtDNA deletions and histological abnormalities were consistently observed across all groups. In monoallelic cases, no evidence of a digenic effect involving AFG3L2 was found. Both autosomal dominant and recessive inheritance patterns were documented, with monoallelic cases typically presenting with a milder phenotype.
Keywords: Általános orvostudomány